2010
DOI: 10.1111/j.1747-4949.2010.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Skeletal Muscle Mass after Stroke: a Systematic Review

Abstract: Loss of muscle mass after stroke has implications for strength and functional ability and may also contribute to impaired glucose metabolism. Therefore, prevention of muscle loss is desirable. Before interventions to prevent loss of muscle can be designed and evaluated, the expected rate, magnitude and timing of muscle loss need to be understood. A systematic search was undertaken to identify all studies that investigated changes in skeletal muscle mass, volume or cross-sectional area in people after stroke. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(134 citation statements)
references
References 47 publications
6
124
0
4
Order By: Relevance
“…Longitudinal studies of changes in muscle mass over time could not be pooled for metaanalysis because of differences in outcome measures, patient characteristics, and timing of measurements. 21 Our review extends the findings of English and colleagues 21 by considering the interrelationship of stroke and age-related sarcopenia and by examining other important architectural components, including changes in pennation angle, fibre length, and tendon length, that occur after stroke and commenting on how these changes affect force generation. Specifically, the purpose of this review is to examine post-stroke changes in muscle size, muscle fibre length and orientation, and tendon length and to understand how these changes in muscle architecture may influence the angle-torque and force-velocity relationships for the generation of force, which is important in performing functional activities of daily living (ADL).…”
Section: Ré Sumémentioning
confidence: 93%
See 1 more Smart Citation
“…Longitudinal studies of changes in muscle mass over time could not be pooled for metaanalysis because of differences in outcome measures, patient characteristics, and timing of measurements. 21 Our review extends the findings of English and colleagues 21 by considering the interrelationship of stroke and age-related sarcopenia and by examining other important architectural components, including changes in pennation angle, fibre length, and tendon length, that occur after stroke and commenting on how these changes affect force generation. Specifically, the purpose of this review is to examine post-stroke changes in muscle size, muscle fibre length and orientation, and tendon length and to understand how these changes in muscle architecture may influence the angle-torque and force-velocity relationships for the generation of force, which is important in performing functional activities of daily living (ADL).…”
Section: Ré Sumémentioning
confidence: 93%
“…Since declines in muscle mass parallel deficits in force in studies on ageing, we would expect similar findings after stroke. Indeed, a recent systematic review and meta-analysis performed by English and colleagues 21 demonstrated that lean tissue mass of paretic muscle was significantly less than that of non-paretic muscle, in both upper and lower extremities, in people at least 6 months post stroke. Longitudinal studies of changes in muscle mass over time could not be pooled for metaanalysis because of differences in outcome measures, patient characteristics, and timing of measurements.…”
Section: Ré Sumémentioning
confidence: 99%
“…Indeed, a recent systematic review searching 17 042 related publications reported a mere 14 clinical studies with a total of 490 patient participants, which investigated stroke-induced skeletal muscle changes. 29 This survey included both cross-sectional and longitudinal studies. Notably, none of these studies investigated the early (<6 months) changes in muscle function and structure after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of muscle mass after stroke is largely dependent on reduced physical activity. Muscle weakness and loss of strength concern mainly the affected limbs, but apply to both sides [38,39]. The pain connected with the presence of osteoarthritis is the primary cause of reduced physical activity and associated decrease of muscle mass [36].…”
Section: Muscle Function Is Debilitated In Many Diseasesmentioning
confidence: 99%